PELAYANAN ADMINISTRATIF BAGI MASYARAKAT DI KECAMATAN GALANG KOTA BATAM - Ladon, Karol Teovani; Putra, Bobby Mandala (Universitas Jenderal Ahmad Yani, 2019)
This study aims to analyze administrative service efforts provided and constraints faced by Galang District. The results of the study indicate that efforts in administrative services include: submitting application files through (entrusted) to the local kelurahan, file storage through providers of pompong, joint ceremonies and meetings at the beginning of each month (first and second week), providing official housing around sub-district complexes, files can be submitted at the official residence of the employee outside of service hours and socialization has been carried out to improve understanding of service information. This condition shows that there is an interaction between the community and the apparatus in finding a shared solution related to services that can benefit. The obstacles faced include: first, inadequate internet network and only re-installed at the beginning of 2018. Secondly, electricity which still relies on generators and is only affordable by PLN at the end of 2018. Thirdly, damaged E-KTP recording devices so the community must move to the nearest sub-district to do the recording. Fourth, the lack of public understanding of the service system concerning the terms and procedures that must be passed so that the assumption arises that the service is difficult. This has an impact on the comfort and speed of service. The low level of public understanding of the service system is the responsibility of the apparatus to translate it so that it is easily understood.